(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted to legal aspects of the state’s social work in the attitude toward the institute of family are researched. Basic methodological points are formulated. The conclusion about the reasonability of implementation of family policy is made and its main directions are suggested. Keywords: family, state, strategy, family protection, family policy.